Mortality and morbidity of African small ruminants under various management systems - Wilson, R.T.; Traoré, A.; Mukasa, E. (Revue d'Elevage et de Medecine Veterinaire des Pays Tropicaux, 1993)
The paper examines levels of mortality and morbidity from birth to maturity of African small ruminants in a range of traditional (Pastoral, agropastoral, mixed smallholder and modern (research station, ranch) systems. Goat mortality is ususally heavier than that of sheep prior to weaning where two-species of flocks are managed as one unit, due in some areas to the higher numbers of twin births, in others to peste des petits ruminants and occasionaly to a more severe incidence of abortions. Environmental influences affecting the death rate include year, season, type of birth and sex of young, parity or age of dam, and weight of young or dam. Major pathological causes of death and debility include diseases of the pulmonary complex, helminthiasis and sheep pox. Causes described as "unknown" and animals defined as 'lost" amount to as much as 30 percent of animals Reported dead even in modern management systems. Preweaning mortality can be as high as 40 percent of kids born and more than 30 percent of lambs; levels are not noticeably higher in traditional than in modern systems. Adult mortality is usually of the order of 10 percent to 12 percent per year. Improved management, particularly in the perinatal period and during the first month of life, is required everywhere. Better nutrition of dams and young at strategic stages would reduce losses from weakness and debility. More rigorous efforts are required to identify the pathological agents causing death in different species and classes of stock. Combined management /nutrition/ /prophylactic programmes based on findings in these areas would lead to reduced mortality, leaving more stock for future reproduction and offtake. Pluridisciplinary research to diagnose the problems inhibiting systems as well as animal production should lead to most rapid results.